PENGARUH IMBANGAN PROTEIN DAN ENERGI TERHADAP EFISIENSI PENGGUNAAN RANSUM PADA DOMBA GARUT BETINA - Budi Ayuningsih; Iman Hernaman; Diky Ramdani; Siswoyo Siswoyo (JURNAL ILMIAH PETERNAKAN TERPADU, 2018)
This research aimed to study the effect of protein and energy on Diet Use Efficiency of female Garut sheep. Four different treatments diets of different protein to TDN (energy) ration such as R1=11.53%:63.13%; R2=10.78%:70.06%; R3=13.54%:63.18%; and R4=13.67%:69.18% were allocated to 20 heads of female Garut sheep with 7-8 months old and average body weight 15.72 ± 1.33 kg. Completely randomized design was used and collected data  was analyzed with Duncan’s test. The results showed that highest diet use efficiency and protein consumption (P<0.05) were seen in R4 treatment, 13.09% and 94.04 g/day. Meanwhile, TDN consumption did not have any different among R4 (480.23 g/day), R2 (474.80 g/day), and R1 (446.77 g/day) but they were higher (P<0.05) than R3 (370.87 g/day). In other hand, TDN digestibility of R2 and R3 were higher than R1 and R3. In conclusion, protein to TDN ratio of 13.67%:69.18% resulted highest diet use efficiency. Keywords: Female Garut Sheep, Digestibility, Protein, Total Digestible Nutrient